2022
DOI: 10.1186/s40359-022-00893-7
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial needs of adolescent and young adult kidney transplant recipients, and associated interventions: a scoping review

Abstract: Background Renal transplantation is considered the gold standard treatment for end-stage kidney disease. Adolescent and young adult kidney transplant recipients have the highest rate of graft loss amongst transplanted patients. It is largely accepted this is due to psychosocial and behavioural difficulties, which impact adherence to prescribed therapies. This phenomenon is not isolated to a particular healthcare system having been observed in multiple countries across different continents. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…The psychosocial adaption of kidney transplant recipients is a dynamic process impacted by a variety of factors and is closely related to quality of life (Pasquale, 2014;Kamran and Ogden, 2016). According to Wurm et al (2022), kidney transplant recipients have adverse psychosocial experiences after surgery and often have more unmet needs related to equality in healthcare, acceptance, and negative emotion. Indeed, prior research found that the prevalence of anxiety ranged from 25 to 50% among kidney transplant recipients (Fanakidou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The psychosocial adaption of kidney transplant recipients is a dynamic process impacted by a variety of factors and is closely related to quality of life (Pasquale, 2014;Kamran and Ogden, 2016). According to Wurm et al (2022), kidney transplant recipients have adverse psychosocial experiences after surgery and often have more unmet needs related to equality in healthcare, acceptance, and negative emotion. Indeed, prior research found that the prevalence of anxiety ranged from 25 to 50% among kidney transplant recipients (Fanakidou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Third, Medicare data do not contain psychosocial variables indicative of transplant appropriateness (eg, Stanford Integrated Psychosocial Assessment for Transplant ) and likelihood of postoperative care adherence. Future studies are needed to determine how to best evaluate psychosocial factors linked with transplant outcomes in adults with IDD and the effect of readiness for a transplant, available support systems, and other psychosocial factors on rates of transplant among this population. Fourth, examining postoperative adequacy of care and treatment adherence was beyond the scope of this study, but is an important consideration for future work.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, we could not control for this in our analysis or examine the extent to which differences in donor type may have affected our findings. Third, Medicare data do not contain psychosocial variables indicative of transplant appropriateness (eg, Stanford Integrated Psychosocial Assessment for Transplant) and likelihood of postoperative care adherence . Future studies are needed to determine how to best evaluate psychosocial factors linked with transplant outcomes in adults with IDD and the effect of readiness for a transplant, available support systems, and other psychosocial factors on rates of transplant among this population.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also attribute the higher risk of graft loss within this age period to transitioning from pediatric to adult care, yet others did not observe a higher nonadherence or graft failure risk within the transition period 10,12–14 . Several papers describe potential risk factors for poor adherence, including patient‐related factors (e.g., poor knowledge, forgetfulness, side effects, psychological difficulties) as well as family related characteristics (e.g., socioeconomic status, parental oversight of medication intake, poor social support) 5,6,15–17 . In contrast to adult patients, morning doses seem to be more difficult for young patients to remember than evening doses as well as weekends being more difficult than weekdays 18 .…”
Section: Introductionmentioning
confidence: 99%